The anthropogenic impact on water quality of the river Danube in Serbia: Microbiological analysis and genotoxicity monitoring - Kolarević S. (Archives of Biological Sciences, 2011)
The aim of this work was to examine the impact of urban wastewaters on the water quality of the Danube River in Serbia. Samples of water and sediments for microbiological analysis and genotoxicity monitoring were collected from 6 sites during spring and/or autumn 2010. Sanitary analysis, i.e. enumeration of total and fecal coliforms and intestinal enterococci, indicated moderate to critical fecal contamination, while organic load assessment (oligotroph to heterotroph ratio, index of phosphatase activity) revealed the category of moderately polluted water. Mercury-resistant bacteria were detected in all water samples, with high numbers at locations positioned downstream of Belgrade. There was no correlation of the microbiological parameters of the sediment and water samples. Genotoxicity monitoring, performed by the comet assay on hemocytes of mussels Sinanodonta woodiana, indicated a significant increase of DNA damage in mussels collected from the studied sites compared with the control group.